Protirakovinové taxánové prírodné látky - Maruna, Michal; Šturdíková, Mária; Ondrejíčková, Petra (Chemické listy, 2010)
Paclitaxel is a valuable plant drug produced by Taxus species, showing anticancer activity in various cancer types. Its action consists in preventing depolymerization of tubulin in cell division. Unfortunately, its isolation from the bark of slow-growing yew trees is limited. Although paclitaxel has been totally synthesized, its production currently depends, completely or in part, on supply of Taxus sp. Plant cell cultures, endophytic and epiphytic microorganisms as well as chemical and biotechnological synthesis are currently investigated for the production of taxanes (paclitaxel and docetaxel).
Keywords: Financing, Organized; Neoplasms; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; toxoidy; financování organizované; Toxoids; Paclitaxel; Biotechnology; nádory; paclitaxel; biotechnologie